Fishscapes: Noticing Multispecies Entanglements in a Nair Taravad - Sunil D. Santha (Kronos)
This paper narrates the interspecies relatedness and gendered entanglements in the life journey of anchovies from the oceans to the plate. In dynamic capitalist sites, anchovies are transformed from their very being into cheap resources and are translated as new commodity frontiers with varying social and ecological consequences. Anchovies were once part of the staple diet of the Nair households, which I describe in this paper. My inquiry for this paper begins here. How did the anchovy disappear from our everyday life? What does it say about gender inequality, modernity, and environmental change? Fishscapes, in this paper, are stories that Nair women have to say about their fish-making practices, reminiscing about their social encounters with anchovies. Autoethnographic by design, this paper explores the situated perspectives of Nair women's relatedness with anchovy as the starting point to understand how their daily experiences and ways of knowing interface with historical and layered patches of modernisation, patriarchy, and environmental change in a more-than-human world.